Guna dan citra sebagai wujud kreativitas dalam arsitektur nusantara: Studi kasus arsitektur Tongkonan Toraja, Mamasa dan Batak Toba - Josephine Roosandriantini (EMARA: Indonesian Journal of Architecture, 2020)
Nusantara architecture, which is the result of creative ideas from the Nusantara people, tends to be created with simple materials and equipment. However, the Nusantara architecture, which comes with its ancient identity, does not mean that it has no creative value. This study explores the application of Mangunwijaya's "Use and Image" theory in seeing the form of creativity in Nusantara architecture. The data was collected through various literature reviews to conclude how the "Use and Image" theory was applied in Nusantara architecture. Two traditional architectural objects, namely the Tongkonan in Toraja and Mamasa, and the Batak Toba architecture were chosen as study objects. The study results show that the Guna aspect's application lies in the architectural details of the construction, the roof appearance, and materials function-related. Meanwhile, the application of image lies in describing the meaning associated with the building finishing. This further study strengthens the fact that Nusantara architecture is the result of the Nusantara creative ideas in adapting to geographical and climatic conditions